2013
DOI: 10.1111/bju.12039
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based comparison of laparoscopic and open pyeloplasty in paediatric pelvi‐ureretic junction obstruction

Abstract: Objective• To describe the extent of use and in-hospital outcomes of open and laparoscopic pyeloplasty for paediatric pelvi-ureteric junction (PUJ) obstruction in the USA. Patients and Methods• Results• During the 5-year study interval, 4426 (96.4%) and 164 (3.6%) paediatric patients diagnosed with PUJ obstruction underwent open and laparoscopic pyeloplasty, respectively.• The proportion of patients undergoing laparoscopic pyeloplasty gradually increased from 2.4% in 2004 to 4.4% in 2008, but this increase wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
0
23
1
5
Order By: Relevance
“…Success rates were similar in laparoscopic and open pyeloplasty. This success rate in GH is lesser than post pyeloplasty in simple HDN (>93%) as reported by Knoedler et al [25] and Pohl et al [26] . Complication rate reported as 23.8 % in our series is higher than reported in simple HDN by Pohl et al [26] .…”
Section: Discussionmentioning
confidence: 61%
“…Success rates were similar in laparoscopic and open pyeloplasty. This success rate in GH is lesser than post pyeloplasty in simple HDN (>93%) as reported by Knoedler et al [25] and Pohl et al [26] . Complication rate reported as 23.8 % in our series is higher than reported in simple HDN by Pohl et al [26] .…”
Section: Discussionmentioning
confidence: 61%
“…This is now the most common presentation of ureteropelvic junction (UPJ) obstruction. The most common etiology for infant hydronephrosis is UPJ obstruction which accounts for approximately 2.5/100,000 of the hospitalization per year (2)(3)(4). The majority of the hospitalizations occur in children less than 3 years old (5).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In contrast to other minimal invasive techniques that have been established as standard of care such as laparoscopic appendectomy, the rather restrictive dissemination of LP might reflect the challenging character of this operation. 8,12 Moreover, a group from Rochester recently showed that the minority of LP takes place in non-teaching hospitals. 12 Against the background of a decentralized hospital system in Germany, this may contribute to the low percentage of LP in infants.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 Moreover, a group from Rochester recently showed that the minority of LP takes place in non-teaching hospitals. 12 Against the background of a decentralized hospital system in Germany, this may contribute to the low percentage of LP in infants. 13 Accordingly, the mode of pyeloplasty may be chosen for the surgeons' discretion and experience instead of the available evidence.…”
Section: Discussionmentioning
confidence: 99%